Open(ing) Education: Theory and Practice - Alla-Mensah, Joyceline (Critical Studies in Teaching and Learning, 2023)
Open(ing) Education: Theory and Practice is edited by Dianne Conrad and Paul Prinsloo. Drawing upon their own extensive engagement in this field, they have produced and edited a wonderfully diverse and comprehensive collection of authors with varying perspectives and experiences. In so  doing, the  book responds  to  the  under  theorisation  of  open  education  by offering very sophisticated and nuanced conceptualisations of open education across the different chapters and in mapping out its different forms. One of the strengths of the book is the different angles from which openness is explored. Throughout the book, the authors add flesh to the idea that open  and  closed  education are  not  the binary opposites of one  another and illustrate  that opening  education is an ongoing project  that embodies  a coexistence of different form sand practices.